Percutaneous Transesophageal Gastric Tubes: Indications, Technique, Safety, Efficacy, and Management - Burns, Kevin M.; Huang, Steven Y. (Digestive Disease Interventions, 2018)
Percutaneous transesophageal gastric (PTEG) tube placement is an alternative method of gastric access for feeding or decompression in patients with contraindications to conventional gastrostomy tube placement such as peritoneal carcinomatosis, gastric wall tumors, ascites, or intervening organs. PTEG tube placement is safe with a high technical success rate and it can be placed with supplies available in most interventional radiology departments using ultrasound and fluoroscopic guidance. PTEG tubes are highly efficacious at reducing symptoms in patients with malignant bowel obstruction as an alternative to long-term nasogastric decompression.
Keywords: transesophageal gastric tube; decompression; venting; feeding